Redefining Spinal Cord Stimulation “Trials”: A Randomized Controlled Trial Using Single‐Stage Wireless Permanent Implantable Devices - North, Richard B. (Neuromodulation, 2019)
BACKGROUND: “Traditional” spinal cord stimulation (SCS) trials with percutaneous electrodes externalized to a pulse generator (PG) are typically limited in duration due to risk of infection. Newer miniaturized wireless SCS technology eliminates the percutaneous extension (as well as PGs implanted for chronic use), thus facilitating a single‐stage implantation after which the device can remain indefinitely. OBJECTIVE: To evaluate fully implanted wireless SCS devices during a 30‐day screening trial in subjects with chronic low back pain and leg pain and a history of lumbosacral spine surgery. METHODS: In a randomized controlled trial of single‐stage wireless SCS using a wireless percutaneous system, 99 subjects received either 10 kHz high frequency stimulation (HFS) or lower frequency stimulation (LFS) below 1500 Hz (Bolash R, Creamer M, Rauck R, et al. Wireless high frequency spinal cord stimulation (10 kHz) compared to multi‐waveform low frequency spinal cord stimulation in the management of chronic pain in failed back surgery syndrome subjects: preliminary results of a multicenter, prospective, randomized controlled study. Pain Med 2019, https://doi.org/10.1093/pm/pnz019). In this report, we assess the 30‐day trial success rate (≥50% pain relief from baseline) and complications. RESULTS: The overall trial success rate was 88% (87/99): 92% (46/50) for HFS and 84% (41/49) for LFS (NS). The trial success rate in the 64 subjects with predominant low back pain was 92% (59/64) vs. 80% (28/35) in those with leg pain ≥ low back pain (NS). During the screening trial, one infection occurred (1%) and one subject withdrew and was explanted (1%). Electrode migrations were seen on routine follow‐up x‐rays in 10 cases (10%). CONCLUSION: Using wireless SCS devices that allow for an extended trial period and evaluation of various waveforms, we observed a high rate trial success rate with both HFS and LFS waveforms, with minimal incidence of infection. Long‐term follow‐up will address the cost‐effectiveness and morbidity associated with this technology, which facilitates single‐stage treatment.